Web 2.0 in the CRM domain: defining social CRM. (1st January 2011) - Faase, Robbert; Helms, Remko; Spruit, Marco
Businesses are becoming more customer-centric and see a need to address customers more individually. An opportunity is identified in Web 2.0 technologies. Both CRM and Web 2.0 have been researched broadly in the past years, but not their potentially successful combination, which we call 'social CRM'. It is a CRM strategy which encourages customer collaboration and involvement. Based on empirical research we found that Web 2.0 services add value in every domain of the CRM environment, depending on the type of service at hand. Most value is added in the marketing domain of CRM. Social networks, blogs, and multimedia sharing add most value across all domains. This research defines social CRM and presents a new model that depicts the fundamental aspects of social CRM in four layers. We conclude with suggestions for further research in this emerging research domain.